Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/rjdnmd-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nutrition Knowledge and Development of Complications in Type 2 Diabetic Patients

Abstract: Background and Aims: Diabetes is increasing rapidly in Turkey as most countries in the world. The prevention of complications which is the main aim in the treatment of diabetes can be accomplished partly with nutrition education. The aim of this study was to assess the relationship between nutrition knowledge (NK) and complications in patients with type 2 diabetes. Materials and Methods: 280 patients with 8-20 years of diabetes duration who applied to diet outpatient clinic were recruited. The questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As the majority of morbidities and mortalities due to T2DM are attributed to micro- and macrovascular complications, it is important to expand the focus of care beyond glycemic control. A positive correlation between insufficient nutritional knowledge and diabetic foot [odds ratio 3.86 (95% CI 0.99–14.98), p = 0.051] and coronary artery disease [odds ratio 2.23 (95% CI 1.13–4.40), p = 0.021] was observed in women with diabetes [77]. Results from landmark studies such as the Diabetes Control and Complications Trial (DCCT) and the UK Prospective Diabetes Study (UKPDS) have provided compelling evidence for the role of MNT in preventing micro- and macrovascular complications of diabetes [21, 78].…”
Section: Medical Nutrition Therapy For Complications Of T2dmmentioning
confidence: 99%
“…As the majority of morbidities and mortalities due to T2DM are attributed to micro- and macrovascular complications, it is important to expand the focus of care beyond glycemic control. A positive correlation between insufficient nutritional knowledge and diabetic foot [odds ratio 3.86 (95% CI 0.99–14.98), p = 0.051] and coronary artery disease [odds ratio 2.23 (95% CI 1.13–4.40), p = 0.021] was observed in women with diabetes [77]. Results from landmark studies such as the Diabetes Control and Complications Trial (DCCT) and the UK Prospective Diabetes Study (UKPDS) have provided compelling evidence for the role of MNT in preventing micro- and macrovascular complications of diabetes [21, 78].…”
Section: Medical Nutrition Therapy For Complications Of T2dmmentioning
confidence: 99%
“…On the other hand, in diabetic rats, the beneficial effects of B. vulgaris extracts showed positive effects in attenuating the side effects of T2DM (Karami et al, 2016), ameliorating oxidative stress (Hemmati et al, 2016), decreasing the liver damage by influencing hepatic histopathological and biochemical markers (Rahimi-Madiseh et al, 2017), and showed that the serum cholesterol and serum triglycerides levels were decreased (Meliani et al, 2011).…”
Section: In Vivo Activities Against Diabetes and Metabolic Diseasesmentioning
confidence: 99%
“…In this regard, use of medicinal plants and their derivatives such as essential oil, alcoholic, aqueous, and hydroalcoholic extracts has obtained more attention by scientists. I and my colleagues published several studies on the in vivo effects of some medicinal plants such as Satureja khuzestanica (Hafezi et al 2015), Berberis vulgaris (Karami et al 2016), and Galega officinalis and Trigonella foenum-graecum (Shojaee et al 2015) in diabetes mellitus, Zizyphus jujuba (Koohi-Hosseinabadi et al 2015a), Carum carvi , Olea europaea (Showraki et al 2016), and other species (Sepehrimanesh 2016) in oral mucositis, Satureja khuzestanica and Pistacia atlantica (Nazifi et al 2012) in thyroid dysfunction, Thymus vulgaris (Koohi-Hosseinabadi et al 2015b) in hyperlipidemia, Berberis vulgaris (Yazdani et al 2013) on intestinal morphology plus in vitro antimicrobial activity of Scutellaria luteo-caerulea and Calotropis procera ), antihelminthic effect of Peganum harmala (Roozitalab et al 2017) and antioxidant properties of Scutellaria luteo-caerulea ), Calotropis procera (Kazemipour et al 2015) and Mentha piperita (Najafian et al 2016) and Stevia rebaudiana (Najafian et al 2016). Now, we know that these effects are due to mineral elements, phenolic compounds, or other active substances (Kazemipour et al 2015;Najafian et al 2016;Nikbin et al 2014b).…”
Section: Technical Notementioning
confidence: 99%